A Comparative Analysis of Quality of Life in Children Managed for Omphalocele and Gastroschisis - Melanie Kapapa; Teresa Rieg; Alexandre Serra (Wolters Kluwer Medknow Publications, 2024)
Background: Evaluation of quality of life (QoL) in paediatric surgical patients has not always received enough attention in the past. Our aim was to follow up patients with abdominal wall defects for a decade and (1) to analyse children's view on QoL and to analyse parent's view on QoL, (2) to evaluate satisfaction and psychological problems, (3) to assess present complaints including subjective aspects such as food intake, reduced appetite, pain in scar area and general abdominal pain and (4) verifiable clinical symptoms assessed through a physical examination and ultrasound. It was hypothesised that QoL would differ from gastroschisis (GS) and omphalocele (OC) children depending on the type of abdominal wall defect. Materials and Methods: A retrospective case-control design was used to compare children with GS (n = 36) and OC (n = 18). A clinical examination, including abdominal inspection, palpation and auscultation of bowel sounds with abdominal ultrasound, was offered, combined with a structured interview and specific QoL questionnaire (KINDL®). The focus was on QoL, child development, present complaints and satisfaction with the cosmetic outcome. Results: During clinical examinations with ultrasound, GS children were significantly more likely to have bowel loops stuck at the scar area (P = 0.008) with bowel malrotation and abnormal appendix position, compared to OC children (P = 0.037). They were significantly more likely to report irregular stools (P = 0.02) but were satisfied with the cosmetic outcome of the abdominal skin scar in 81% of cases. The KINDL® evaluation showed in the dimensions of QoL, namely 'body awareness', 'mental health', 'self-esteem', 'family', 'friends' and 'school', that there were no significant differences to healthy children. OC/GS parents were satisfied with their children's physical development and QoL, noting no limitations in normal daily activities. Parents of OC children reported suffering from OC/GS-associated problems (P = 0.028) at the time point of interview. Conclusion: Subjective QoL did not differ significantly between OC and GS children. The satisfaction with the cosmetic outcome of the abdominal skin scar was good. On ultrasound examination, adherent bowel loops and bowel malrotation with resulting stool irregularities affect GS children. OC children's parents reported suffering from OC/OS-associated problems, and all parents need to be educated about the symptoms of recurrent sub-ileus events or atypical appendicitis.